Peningkatan Hasil Belajar Siswa Pada Materi Kebhinnekaan Indonesia Dengan Metode Sosiodrama Kelas VII-E Semester Genap Tahun Pelajaran 2022/2023 Di SMP Negeri 40 Surabaya - Akhmad Qomaru Zaman (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
In the Industrial Revolution 4.0, Indonesian people are faced with technological sophistication that makes them able to do anything and communicate without meeting. However, unlimited convenience has a negative impact on the social society of Indonesia based on diversity. The space for communication is increasingly limited because we rarely see others, and everyone becomes individualist and less sensitive. It is necessary to strengthen through sociodrama-based PPKn learning on diversity material to strengthen a sense of unity and unity. The purpose of this Classroom Action Research (PTK) is to improve learning outcomes on Indonesian diversity material with the sociodrama method of grade VII-E students in the even semester of the 2022/2023 academic year at SMP Negeri 40 Surabaya. The subject of research is students. The data collection uses tests and non-tests. Analytical techniques use qualitative and quantitative. The results showed an increase in learning outcomes on average 59.5 in the first cycle to 77.3 in the second cycle. For the highest value of 79 in the first cycle to 90 in the second cycle. As well as the value in the first cycle 30 in the first cycle to 62 in the second cycle. Sociodrama improves PPKn learning outcomes in Indonesian diversity material for grade VII-E students in the even semester of the 2022/2023 academic year at SMP Negeri 40 Surabaya.